Soil water deficit stress on bambara groundnut (vigna subterranea [L.] verdc) and groundnut (arachis hypogaea [L.]) - Kundy, Aloyce Callist (2019)
It is projected that, by year 2100 global population will reach 11.2 billion people. Climate change is projected to increase temperature and reduce water availability. The effects of climate change (e.g. frequent droughts) on crop yields in the world is largely negative. And these effects have resulted to destructing social, environmental and economic problems such as famines, energy crisis, insufficient water supply and ruination of ecosystems. With increasing world population and climate change, strategies to cope with the changing climate cannot be overlooked. Crop intensification and diversification are of first priority. Leguminous crops such groundnut (Arachis hypogaea (L.)) (GT) and bambara groundnut (Vigna subterranea (L.) Verdc) (BGT) are grown in relatively dry, semi-arid areas and display a suit of drought resistance mechanisms that allow them to produce yield under low rainfall conditions. Although variations in drought resistance exist within species and between species, traits and mechanisms involved are not well studied. Five trials were conducted to study the effects of water deficit stress on GT and BGT landraces. Experiments used split plot in randomized complete block design. Four bambara groundnut landrace-derived genotypes viz NALBAM 2, NALBAM 4, DodR, S19-3 and one groundnut variety, MNANJE, were assigned to subplots and three water regimes to main plots. Water treatments were; well-watered throughout, water stress imposed during flowering and water stress imposed during pod development. Soil water deficit significantly (p < 0.001) affected the plants’ performance. Flowering stage proved to be more sensitive to insufficient water supply. This means that, by ensuring enough water supply during flowering could improve crop performance under dry areas. Water deficit stress increased proline (µmoles gram-1 tissue) content by 123% in stressed plots. Highest percent increase in proline was found in MNANJE (174%) and lowest percentage proline increase in NALBAM 4 (89%). Percentage decrease in the rate of photosynthesis (µmol CO2 m-2 s-1) ranged between 60% (MNANJE) and 85% (DodR). Water deficit decreased stomatal conductance (molH20 m-2 s-1) by 90% during flowering and by 64% during pod development. Stomatal conductance was reduced up to 86% (in MNANJE) and up to 90% (in DodR). The highest percent decrease in transpiration rate (mmolH20 m-2 s-1) (88%) was revealed in NALBAM 4 and lowest in MNANJE (46%). Percentage change in relative water content ranged between 20% in MNANJE and 34% in NALBAM 4. The highest percentage decrease in chlorophyll content (10%) was recorded in DodR and the lowest (3%) in S19-3. Chlorophyll content in MNANJE increased by 11% and 6% as a result of insufficient water supply during flowering and pod development, respectively. This implies that, genotypes/species that can maintain appreciable leaf chlorophyll content during drought are able to sustain phostosynthesis and hence overall yield. The highest percentage decrease (26%) in rooting depth (cm) was observed in NALBAM 4 while MNANJE gave the minimum reduction (13%). MNANJE gave the highest root volume (46.64 cm3) with lowest percent decrease (24%), while S19-3 gave percentage decrease in root volume of 49%. Water deficit stress also reduced the root surface area which ranged between 17% (S19-3) and 23% (NALBAM 4). Water deficit stress increased root length density in NALBAM 4 (by 82%) and DodR (by 73%). Lower percentage increase was observed in S19-3 (58%) and MNANJE (52%). During flowering stage, S19-3 had the highest percentage increase in root diameter (37%) while MNANJE gave the highest percentage increase in root:shoot (40%). Grain yield (t ha-1) of both species significantly (p < 0.001) decreased with insufficient water supply. DodR was the most affected (65%), while the yield of MNANJE and S19-3 was reduced by 55% and 59% respectively. By maintaining appreciable amount of relative water content, early maturing, accumulation of high leaf proline content and deeper roots, S19-3 and MNANJE exhibit drought escape, avoidance and tolerance drought resistance mechanisms. The current findings suggest that, MNANJE and S19-3 are drought resistant and can be grown in drought prone areas. The variations observed in the studied parameters among landrace-derived genotypes could be exploited in breeding drought resistance varieties for cultivation in drought-prone areas ultimately improving food security.